2017
DOI: 10.2174/1381612822666161201152941
|View full text |Cite
|
Sign up to set email alerts
|

Is Metformin a Perfect Drug? Updates in Pharmacokinetics and Pharmacodynamics

Abstract: Metformin, a synthetic biguanide, is currently one of the most frequently recommended medications for type 2 diabetes treatment around the world. This review presents the latest discoveries in the pharmacokinetics of metformin, especially the role of transporters (e.g. Organic Cation Transporters OCTs, Multidrug and Toxin Extrusion transporters MATE) in oral absorption, distribution, elimination and biochemical effects of metformin in humans. We also review the associations between genetic variations of metfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 0 publications
1
72
0
18
Order By: Relevance
“…Metformin is a biguanide that decreases hepatic glucose output, decreases intestinal glucose absorption, and increases peripheral glucose uptake in muscles and adipocyte cells 50. Metformin is a hydrophilic compound with low molecular weight and low binding capacity to plasma proteins, and trans-placental passage occurs in a dose dependent manner that is most likely carrier dependent 51.…”
Section: Metforminmentioning
confidence: 99%
“…Metformin is a biguanide that decreases hepatic glucose output, decreases intestinal glucose absorption, and increases peripheral glucose uptake in muscles and adipocyte cells 50. Metformin is a hydrophilic compound with low molecular weight and low binding capacity to plasma proteins, and trans-placental passage occurs in a dose dependent manner that is most likely carrier dependent 51.…”
Section: Metforminmentioning
confidence: 99%
“…Its low lipophilicity does not favor absorption from the small intestine by rapid passive diffusion across cell membranes; consequently, its bioavailability is low, with a mean value of 55% . Therefore, researchers try to modify the formulation of metformin to enhance its bioavailability . The most common side effect of metformin is gastrointestinal distress.…”
Section: Introductionmentioning
confidence: 99%
“…6 Therefore, researchers try to modify the formulation of metformin to enhance its bioavailability. 8 The most common side effect of metformin is gastrointestinal distress. Hypoglycemia and lactic acidosis are rare, and the latter mainly occurs in patients with renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…The associations between T2DM and concomitantly occurring haemostasis disturbances, including thrombosis and the activation of blood coagulation are widely known [1]. Lipiński and Pretorius [2] divide the characteristic haemostatic abnormalities in T2DM into those occurring in stages of coagulation: thrombus formation, impaired fibrinolysis, endothelial dysfunction and platelet hyperreactivity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was reported that platelets in diabetes subjects are characterized by hyperreactivity, increased adhesiveness, exaggerated aggregation and changed metabolism [3]. T2DM patients can also present a pro-coagulation state following increased activity of coagulation factors such as fibrinogen, vWF, or factor FVII [1]. In T2DM patients, increased fibrin levels and thrombin generation have also been reported [3].…”
Section: Introductionmentioning
confidence: 99%